The influence of social networks in facilitating training transfer and goal setting amongst small businesswomen: a conceptual framework / Norlina Mohamed Noor and Raja Munirah Raja Mustapha - Mohamed Noor, Norlina; Raja Mustapha, Raja Munirah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Knowledge and skills have become the most crucial resource capital which enables organizations to survive in the ever changing business environment. One of the common strategies for organizations to increase their performance and productivity is through training and the main role of human resource development is to fulfil the needs of the organizations by providing employees with up to date expertise, information, knowledge and skills. Since huge financial investments and enormous time are allocated for training, organizations hope that the training will lead to the desired work outcomes. However, this does not always happen. There is only a small percentage of training programs which had successfully shown lasting transferability to the workplace and this indicates that understanding and improving the training transfer process is still a major concern for training researchers and practitioners. As training transfer is influenced by several variables at different levels of analysis, this study attempts to investigate the relationship between training transfer determinants, the involvement of different stakeholders and training activities in the training process. Specifically, this study investigates the influence of training transfer determinants on goal setting amongst small businesswomen. In addition, it will emphasize the roles of primary stakeholders in the social network at different times during the training process towards achieving training transfer. Therefore, the framework postulates social networks as a moderating variable in enhancing training transfer and goal setting amongst small businesswomen.